The Making of the Modern State - Nelson, B. author. aut Link
X, 181 p.
Keywords: Nelson provides a historical overview of the theoretical and ideological evolution of the modern state, from pre-state and pre-modern state formations to the present. A major theme of the book is the need to understand the modern state holistically, as a totality of social, political, and ideological factors.